2011
DOI: 10.1021/cg101230j
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxially Grown Films of Standing and Lying Pentacene Molecules on Cu(110) Surfaces

Abstract: Here, it is shown that pentacene thin films (30 nm) with distinctively different crystallographic structures and molecular orientations can be grown under essentially identical growth conditions in UHV on clean Cu(110) surfaces. By X-ray diffraction, we show that the epitaxially oriented pentacene films crystallize either in the “thin film” phase with standing molecules or in the “single crystal” structure with molecules lying with their long axes parallel to the substrate. The morphology of the samples observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 48 publications
7
39
0
Order By: Relevance
“…Pentacene (5A), a conjugated organic small molecule, is the most outstanding active layer material used in OTFTs, due to its relatively high field effect mobility and ability to form well-ordered films [5,6]. Because the charge transport in organic films depends strongly on the π/π overlap among the neighboring molecules, an optimum effect can be achieved in the directions with maximum π/π overlap, which is often perpendicular to the long molecular axis or the molecular plane [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pentacene (5A), a conjugated organic small molecule, is the most outstanding active layer material used in OTFTs, due to its relatively high field effect mobility and ability to form well-ordered films [5,6]. Because the charge transport in organic films depends strongly on the π/π overlap among the neighboring molecules, an optimum effect can be achieved in the directions with maximum π/π overlap, which is often perpendicular to the long molecular axis or the molecular plane [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Because the charge transport in organic films depends strongly on the π/π overlap among the neighboring molecules, an optimum effect can be achieved in the directions with maximum π/π overlap, which is often perpendicular to the long molecular axis or the molecular plane [7,8]. The molecular orientation of the pentacene film exerts a significant effect on their electronic properties [6], and the desired molecular configuration for OTFTs should be upright-standing to facilitate charge transport [9,10]. In contrast, an undesirable flat-lying orientation appears during the deposition of pentacene on the silicon oxide surface, the causes of which remain unclear [7].…”
Section: Introductionmentioning
confidence: 99%
“…3 The complexity of organic film growth is further enhanced by the well-known polymorphism of organic materials, which can be reflected by the (co-)existence of multiple thin film phases at surfaces. [23][24][25][26][27][28] In spite of the previously mentioned complexities, the general theory of crystal growth can still be applied to organic film growth after appropriate revision. [3][4][5][6][29][30][31][32] Its adaption to organic systems is an ongoing project, requiring input from carefully chosen experiments that help to single out the special features of ordering and growth at the organic/metal interface.…”
mentioning
confidence: 99%
“…By controlling the coverage of pentacene on Cu(119), Annese demonstrates that highly ordered pentacene films can be obtained in a flat orientation for low coverages and in a bulk-like herringbone upright orientation for higher coverages by near-edge X-ray absorption fine structure (NEXAFS) spectroscopy and scanning tunneling microscopy (STM) [34]. Djuric et al shown that under identical growth conditions, two very different oriented films of pentacene on Cu(110) Surfaces can be grown [35]. These dissimilar growth behaviors are induced by subtle differences in the monolayer structures, which can be controlled by preparation procedures.…”
Section: Discussionmentioning
confidence: 99%